Biostratigraphy of larger foraminifera in the Eocene (upper Ypresianlower Bartonian) sequences of the Southern Slope of the Western Caucasus (Russia, NE Black Sea). Correlation with regional and standard planktonic foraminiferal zones - F. ZAKREVSKAYA; S. STUPIN; E.M. BUGROVA (Geologica Acta, 2009)
The biostratigraphic analysis of two Eocene (Upper Ypresian-Lower Bartonian) sections located on the Southern Slope of the Western Caucasus (Inal and Loo sections in the Tuapse and Sochi districts, respectively) was carried out using planktonic and larger foraminifera. The planktonic foraminiferal assemblages recorded in these southern sections were similar to those recorded in the North Caucasian region and enabled to recognize the lower Ypresian to lower Bartonian zones of the local Caucasian biostratigraphic scale. The turbiditic sedimentary processes recorded in these sections affected the composition of larger foraminiferal assemblages, which is mostly represented by nummulitids and orthophragmines. Although the larger foraminiferal assemblages are typical of the Peritethys and also resemble those reported in the Northern Caucasian region, the Tethyan SBZ zonal scheme could be applied and SBZ11 to 15/16 zones were identified (at least late Ypresian to middle Lutetian). This integrated study improves the correlation between the planktonic and benthonic local biostratigraphic scales in the Caucasus and allows their correlation with the standard and other biostratigraphic scales in neighbouring Tethyan regions.